Karyotypic characterization of Ramphastidae (Piciformes, Aves) - Castro, Márcio Siqueira; Recco-Pimentel, Shirlei M.; Rocha, Guaracy Tadeu [UNESP] (Sociedade Brasileira de Genética, 2002)
The karyotypes of nine species of the family Ramphastidae were determined and compared with that of the toco toucan (Ramphastos toco), the only ramphastid karyotype so far reported in the literature. Differences in the morphology of the largest chromosomes allowed to identify three karyotype groups. The first group included the species R. toco, Baillonius bailloni, Pteroglossus castanotis, P. aracari and Selenidera maculirostris, in which only the first pair of chromosomes was metacentric. The second group included four Ramphastos species (R. dicolorus, R. ariel, R. vitellinus, R. tucanus cuvieri) with two pairs of metacentric macrochromosomes (the first and the seventh). The third group was represented by a single species, A. laminirostris, in which all the autosomal chromosomes were telocentric. All of the species had subtelocentric Z chromosomes, similar in size to homologues of the first pair. Sex chromosome W was a small chromosome. The chromosome number ranged from 2n = 62 in P. aracari to 114 in R. toco. The cytotaxonomic relationships among toucan species are discussed, based on chromosome analysis.
Keywords: karyotypes; Rhamphastidae; toucans